Main Features of the Stability and Reliability Enhancement of Electricity Grid with DG in Ukraine Based on IEEE Standards - Kyrylenko, O.V.; Strzelecki, R.; Denysiuk, S.P.; Derevianko, D.G. (Технічна електродинаміка, 2013)
A system of stability and reliability indices for energy systems of Ukraine was explored. The influence of foreign IEEE standards for the formation of the reliability of electricity grid of Ukraine was discussed. A comparative analysis of the reliability standards (IEEE Std 1366) was held and estimated innovation standard IEEE Std 1366-2012 was made, which would be useful for implementation of DG sources in Ukraine. Розглянуто систему показників стійкості та надійності енергетичних систем України. Проаналізовано вплив зарубіжних стандартів ІЕЕЕ на формування показників надійності в Україні. Проведено співставний аналіз стандартів надійності ІЕЕЕ Std 1366 та оцінено нововведення стандарту ІЕЕЕ Std 1366-2012, які були б корисні при впровадженні джерел розосередженої генерації в Україні. Рассмотрена система показателей устойчивости и надежности энергетических систем Украины. Проанализировано влияние зарубежных стандартов IЕЕЕ на формирование показателей надежности в Украине. Проведен сопоставительный анализ стандартов надежности IЕЕЕ Std 1366 и оценены нововведения стандарта IЕЕЕ Std 1366-2012, которые были бы полезны при внедрении источников рассредоточенной генерации в Украине.